Hit-to-lead optimization and discovery of a potent, and orally bioavailable G protein coupled receptor kinase 2 (GRK2) inhibitor. Issue 23 (1st December 2020) - Xu, Guozhang; Gaul, Michael D.; Liu, Zhijie; DesJarlais, Renee L.; Qi, Jenson; Wang, Weixue; Krosky, Daniel; Petrounia, Ioanna; Milligan, Cynthia M.; Hermans, An; Lu, Hua-Rong; Huang, Devine Zheng; et al.
Graphical abstract: Abstract: G-protein coupled receptor kinase 2 (GRK2), which is upregulated in the failing heart, appears to play a critical role in heart failure (HF) progression in part because enhanced GRK2 activity promotes dysfunction of β-adrenergic signaling and myocyte death. An orally bioavailable GRK2 inhibitor could offer unique therapeutic outcomes that cannot be attained by current heart failure treatments that directly target GPCRs or angiotensin-converting enzyme. Herein, we describe the discovery of a potent, selective, and orally bioavailable GRK2 inhibitor, 8h, through high-throughput screening, hit-to-lead optimization, structure-based design, molecular modelling, synthesis, and biological evaluation. In the cellular target engagement assays, 8h enhances isoproterenol-mediated cyclic adenosine 3′, 5′-monophosphate (cAMP) production in HEK293 cells overexpressing GRK2. Compound 8h was further evaluated in a human stem cell-derived cardiomyocyte (HSC-CM) contractility assay and potentiated isoproterenol-induced beating rate in HSC-CMs.